Can Implicit Measures Augment Suicide Detection in Youth? The Feasibility and Acceptability of the Death Implicit Association Test among Pediatric Medical Inpatients - Annabelle M. Mournet; Daniel S. Powell; Elizabeth C. Lanzillo; Sandra McBee-Strayer; Emory Bergdoll; Catherine R. Glenn; Alexander Millner; Maryland Pao; Matthew K. Nock; Lisa M. Horowitz; Jeffrey A. Bridge (MDPI AG, 2022)
Background: Medically ill youth are at increased suicide risk, necessitating early detection. This study aimed to assess the feasibility of administering the Death Implicit Association Test (Death IAT) to pediatric medical inpatients. Methods: Participants completed measures including the Ask Suicide-Screening Questions (ASQ) and the Death IAT. Results: Over 90% of participants found the Death IAT to be acceptable and more than 75% of participants were comfortable completing the task. There was a small, but statistically significant, improvement from pre-survey to post-survey reports of mood (t(174) = 3.02, p = 0.003, d = 0.15). Participants who endorsed a past suicide attempt on the ASQ had significantly higher "suicide" trial D-scores than those without a past suicide attempt (Wilcoxon W = 1312; p = 0.048; d = 0.61). Conclusions: Implementing an IAT measure among pediatric medical inpatients was feasible and acceptable. In exploratory analyses, "suicide" trial IAT D-scores were associated with past suicide attempts, suggesting future studies should examine whether implicit measures may be useful in hospital settings to augment detection of youth suicide risk.